Detecting the Existence of Herding Behavior in Intraday Data: Evidence from the Indonesia Stock Exchange - Setiyono Setiyono; Eduardus Tandelilin; Jogiyanto Hartono; Mamduh M. Hanafi (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2013)
This study attempts to investigate the issue of the existence of institutional herding in the stock market. The existence is detected in the intraday trade data from the Indonesia Stock Exchange (IDX) during up, down, and stable market condition over the period 2003-2005. By using the model of Lakonishok et al. (1992), it is found that the intensity of the existence of institutional herding at the IDX, on average, is 8.4 percent. Institutional investors do not seem to lead their transactions ina certain characteristic of stock. Most of them follow positive-feedback trading strategy while others follow negative-feedback trading strategy. This study also found that the existence of herd behavior at the IDX did not destabilize the market price in a subsequent period.